Transient thermal behavior of a passive heat sink integrated with phase change material: A numerical simulation - Vahid Safari; Babak Kamkari; Masoud Zandimagham; Neil Hewitt (International Journal of Thermofluids, 2023)
This paper presents a numerical investigation of the thermal performance of a heat sink augmented with phase change material (PCM) for passive electronic cooling applications. The PCM-based heat sink employed N-eicosane as the PCM, which has a suitable melting temperature and high latent heat capacity for electronic cooling applications. A numerical simulation based on the enthalpy-porosity method was developed to analyze the impact of both PCM inclusion and induced natural convection airflow on the base temperature of the heat sink. The operational conditions were selected as three constant heat fluxes of 2, 3, and, 4 kW/m2 and four critical base temperatures of 40, 45, 50, and 55 °C. The influence of fin numbers on the thermal behavior of both PCM-based and conventional (without PCM) heat sinks was also investigated by considering the three fin numbers of 4, 5 and, 6. The PCM integration into the heat sink effectively delayed the rise of base temperature and extended the safe operation time compared to a conventional one. The thermal performance enhancement ratio of the PCM-based heat sink over the conventional heat sink ranged from 1.53 to 2.81, depending on the selected heat flux and critical temperature. The effect of fin numbers on thermal performance was more significant at lower heat fluxes. It was observed that the PCM-based heat sinks achieved a higher time-averaged heat transfer coefficient than the conventional heat sinks, and this coefficient increased with the heat flux and decreased with the fin number. For both PCM-based and conventional heat sinks, it was observed that increasing the fin number reduces the heat transfer coefficient value due to the suppressing effect of fins on natural convection current. The results demonstrate the potential of using passive PCM-based heat sinks for improving the reliability and efficiency of electronic devices compared to conventional heat sinks.